In vivo imaging of MMP-13 activity in the murine destabilised medial meniscus surgical model of osteoarthritis. - Lim, N; Meinjohanns, E; Meldal, M; Bou-Gharios, G; Nagase, H (Elsevier, 2014)
OBJECTIVE: To detect and determine disease severity of osteoarthritis (OA) using a probe activated by matrix metalloproteinase-13 (MMP-13) in vivo in the murine destabilised medial meniscus (DMM) surgical model of OA. DESIGN: We have previously described MMP12ap and MMP13ap, internally quenched fluorescent peptide substrate probes that are activated respectively by MMP-12 and MMP-13. Here we used these probes to follow enzyme activity in vivo in mice knees 4, 6 and 8 weeks following DMM surgery. After in vivo optical imaging, disease severity was determined through traditional histological analysis. The amount of probe activation was analysed for discrimination between DMM, contralateral and sham operated knees, as well as for congruence between activity and histological damage. RESULTS: There was no specific activation of MMP12ap at the time points observed between sham operated and DMM operated, or their respective contralateral joints. The activation of the MMP13ap in the DMM model was highest 6 weeks after surgery, but was only specific compared against sham surgery 8 weeks after surgery (1.5-fold increase). The activation of MMP13ap correlated with histological damage 6 and 8 weeks after surgery, with correlations of 0.484 (P = 0.0032) and 0.478 respectively (P = 0.0049). This correlation dropped to 0.218 (P = 0.011) if all data were considered. CONCLUSION: The current MMP-13 activity probe is suitable for the discrimination between DMM and sham or contralateral knees 8 weeks after surgery, when cartilage loss is typified by the appearance of small fissures up to the tidemark, but not earlier. This activity correlates with the histological damage observed.